Pengaruh Anchoring dalam Penilaian Kinerja: Sebuah Studi Eksperimen Kuasi dengan Variabel Tergantung Penilaian Adaptive Performance - Irmalia Nur Sukmananti; Rahmat Hidayat (Gadjah Mada Journal of Professional Psychology (GamaJPP), 2017)
The purpose of this study was to determine the effect of anchoring on the performance appraisal score in aspect adaptive performance. The hypothesis in this study was to examine whether there are differences in the adaptive performance score. High anchoring group has a higher adaptive performance score compared with the low anchoring group. The method used on this study was a quasi experiment with posttest-only design with two treatment groups. Participants involved in this research were 117  with an age range from 22 to 49 years old that classified into high anchoring group (n = 70) and low anchoring group (n = 47). Questionnaire to examine the knowledge of the task was used to conduct a manipulation check of anchoring. Independent-Samples T Test explained no significant effect of anchoring on adaptive performance score (t = -0,100; p > 0,05).